Facilitation vs. apparent competition: Insect herbivory alters tree seedling recruitment under nurse shrubs in a steppe-woodland ecotone - Chaneton, Enrique Jose (2010)
Facilitation of recruitment by 'nurse' plants can play a major role in harsh environments. Yet the extent to which consumer-mediated apparent competition from habitat-forming plants may counteract facilitative interactions remains largely unexplored. We examined whether seedling predation by tenebrionid beetles seeking refuge under nurse shrubs may prevent tree recruitment facilitation in a Patagonian steppe-woodland ecotone. Newly emerged seedlings of Austrocedrus chilensis were planted in shrub canopy, off-shrub shelter and bare soil microsites, and monitored for causes of early mortality and for overall survival under ambient and elevated beetle densities. Most seedlings in open microsites died from abiotic stress, whereas shrub cover and artificial shelters decreased desiccation mortality. Herbivory was the main cause of mortality in shrub microsites. Beetle addition increased predation beneath shrubs and in off-shrub shelters, indicating that apparent competition 'spilled over' from shrubs with high insect densities. Litter removal from shrubs prevented seedling predation suggesting that nurse plants altered recruitment by providing food as well as shelter to insects. Herbivory rates did not depend on seedling patch density but decreased with seedling age, with 1-week old plants being most vulnerable to beetle predation. Synthesis. Apparent competition from nurse plants can strongly reduce recruitment facilitation in stressful environments, although weak herbivore density dependence and seedling growth into ontogenetic refuges may limit the strength of apparent competition. An explicit consideration of negative, as well as positive, herbivore-mediated indirect effects from habitat-forming plants would broaden the understanding of community dynamics along stress gradients. © 2010 The Authors. Journal compilation © 2010 British Ecological Society.